Biomimetic materials design for cardiac tissue regeneration. (30th September 2013) - Dunn, David A.; Hodge, Alexander J.; Lipke, Elizabeth A.
Abstract : Cardiovascular disease is the leading cause of death worldwide. In the absence of sufficient numbers of organs for heart transplant, alternate approaches for healing or replacing diseased heart tissue are under investigation. Designing biomimetic materials to support these approaches will be essential to their overall success. Strategies for cardiac tissue engineering include injection of cells, implantation of three‐dimensional tissue constructs or patches, injection of acellular materials, and replacement of valves. To replicate physiological function and facilitate engraftment into native tissue, materials used in these approaches should have properties that mimic those of the natural cardiac environment. Multiple aspects of the cardiac microenvironment have been emulated using biomimetic materials including delivery of bioactive factors, presentation of cell‐specific adhesion sites, design of surface topography to guide tissue alignment and dictate cell shape, modulation of mechanical stiffness and electrical conductivity, and fabrication of three‐dimensional structures to guide tissue formation and function. Biomaterials can be engineered to assist in stem cell expansion and differentiation, to protect cells during injection and facilitate their retention and survival in vivo, and to provide mechanical support and guidance for engineered tissue formation. Numerous studies have investigated the use of biomimetic materials for cardiac regeneration. Biomimetic material design will continue to exploit advances in nanotechnology to better recreate the cellular environment and advance cardiac regeneration. Overall, biomimetic materials are moving the field of cardiac regenerative medicine forward and promise to deliver new therapies in combating heart disease. WIREs Nanomed Nanobiotechnol 2014, 6:15–39. doi: 10.1002/wnan.1241 This article is categorized under: Therapeutic Approaches and Drug Discovery > Nanomedicine for Cardiovascular Disease Implantable Materials and Surgical Technologies > Nanotechnology in Tissue Repair and Replacement